Consumer Contracts and European Community Law - Andreas P. Reindl (Washington University Law Quarterly, 1997)
The purpose of this Article is to complement the Symposium's discussion of UCC-specific consumer protection issues with an overview of recent consumer protection developments in the European Community.
Keywords: Consumer protection -- European Union countries